The Shift Toward Payment Systems Alternative to tit SWIFT System and Its Role in Redistributing International Financial Power - Suad Jawad Kadhim (International Journal on Economics, Finance and Sustainable Development, 2026)
Tit research aims to study transformation increasing about systems payments tit alternative on system SWIFT analysis turn in re distribution power finance international in shadow variables economic geopolitics accelerated, and it reviews search status system SWIFT As structure basic for communications finance global, and factors that it paid number from countries to search on alternatives for him, and in Introduction sanctions economic and desire in strengthening sovereignty finance, and reduce accreditation on dollar American, and benefit from developments technology in area payments digital. As well it deals search most prominent systems tit alternative, like order Chinese CIPS and tit system Russian SPFS, addition to Initiatives regional and currencies digital Issued on banks centrality, with statement Its goals and its ability on to support transactions tit passerby for tit borders and it analyzes search antiquities potential for this transformation on structure order financial global, from where reducing concentration in influence financial international, and strengthening use currencies local in commerce international, and appearance system financial more pluralism and balance. Likewise discuss challenges that faces this is amazing systems, among them limitations Spread, and requirements trust International, difficulties integration between networks tit different ones, and continuation Status pivotal for tit dollar in economy Global and it depends tit study on curriculum descriptive analytical from during review literature economic finance and reports international tit connection and tit end to that alternatives emerging no represents in tit time current alternative complete for tit system SWIFT, unless that it reflect transformation gradually about pluralism greater in structure finance international, in what may contributes In tit future in reformation scales power finance global expanding margin independence financial for countries tit seeker to diversification channels payments settlements international.